STRATEGI PENGEMBANGAN KOTA SEMARANG MENUJU KOTA M. I. C. E UPAYA PERCEPATAN PEMBANGUNAN MENUJU KOTA SEMARANG SETARA - Prihatin Tiyanto Prihatin Tiyanto (Serat Acitya, 2013)
The title of this research " The strategy of development Semarang city towards M.I.C.E city in the effortincreases acceleration of development commensurable Semarang"Purpose of main this research is to know how the strategy of development Semarang city towards M.I.C.Ecity of development commensurable Semarang. Population and sample this research is tourism industry andstakeholder. Number of samples 50 and returning 42 samples. Sample is taken with purposive sampling that issample has characteristic specially relates to events M.I.C.E in Semarang city. The respondent is government ofsemarang city represented by SKPD, the bisnis tourism and urban community of semarang city which involvein events M.I.C.E, besides also tourist outside a visit to Semarang city. The research approach applies isdescriptive qualitativeness. To know the strategy of development Semarang city has applied SWOT analysis,with FGD and In Depth Interview.Strength and opportunity Semarang city from result of analysis lays in geographical position, the many eventswhich is available, the many place of foods tourism, the many place of events which has not been exploitedmaximumly, and can be hold mutually many investors. The weakness and the threats is the entry of foreignproduct, and new technology, alteration of technology, events big scale pulled in Solo and Jogjakarta city,history and religi tourism fails with other city. The result of analysis shows Semarang city to stay on potitionS<W and O>T so needs internal consolidation and potency Semarang city can be developed furthermore.The SWOT Analysis are more detailed shows Semarang city, with matrix the strategi of developmentSemarang city: a. Improvement of weakness b. Builds of excellence.While Striving acceleration of development commensurable semarang city is by integrating and mapping eventswhich able to be categorized M.I.C.E during certain range of time line. And bravery carries out events M.I.C.Eis having scale national and international in Semarang City. Event M.I.C.E affects at high growth economics,increasing of activity opportunity, increases prosperity of urban community Semarang city.